THE IMPORTANCE OF MAKING ALL PUBLIC UNIVERSITIES FREE - Tuxtamurodova Sarvinoz; Ishqobilova Xulkar Shadullayevna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This study examines the issue of whether public universities should provide free education. In recent years, the idea of free higher education has gained increasing attention due to rising social inequality and the need to expand access to education. The paper explores the advantages of free university education, including the promotion of social equity, the development of a skilled workforce, and its contribution to societal progress. At the same time, it analyzes potential drawbacks such as the financial burden on the state budget, possible declines in educational quality, and limited resources. The study concludes that free higher education can be effective if implemented under specific conditions.